SOCIOECONOMIC STATUS MODERATES THE RELATIONSHIP BETWEEN SELF-ESTEEM AND CONSPICUOUS CONSUMPTION: EVIDENCE FROM AN ELECTROPHYSIOLOGICAL STUDY - Lin, Yiqin (LIFE: International Journal of Health and Life-Sciences, 2024)
There remain inconsistent findings regarding the impact of self-esteem on conspicuous consumption in social psychology and consumer research. The present study explained this issue and revealed that the relationship between self-esteem and conspicuous consumption is moderated by socioeconomic status (SES). Specifically, the relationship between self-esteem and conspicuous consumption is negative when SES is low, while it is positive when SES is high. These findings were verified through a Go/NoGo association task (GNAT) combined with event-related potential (ERP), which capture individuals’ automatic attitudes towards conspicuous products. The present study contributes crucial insights into the mechanisms of how self-esteem interacts with SES to influence individuals’ conspicuous consumption from an implicit perspective. Furthermore, it offers substantial practical implications for the effective management of consumer marketing strategies across diverse socioeconomic contexts.